Smoking Outcome Expectancy: Pengetahuan, Perilaku, dan Konsekuensi dari Merokok - Elmy Bonafita Zahro (Laboratorium Sosiologi Universitas Nahdlatul Ulama Indonesia Jakarta, 2020)
This study aims to see the relationship between smoking outcome expectancy and knowledge about the dangers of smoking in smokers with high, moderate, and low levels of addiction. Smoking outcome expectancy is a construct to explain the expectations a person gets from smoking behavior. This study involved 101 young adult smokers as respondents. Smoking outcome expectancy is measured by the SCQ-A (Smoking Consequences Questionnaire for Adults) measuring instrument compiled by Copeland, et al. (1995) adapted by Jeffries, et al. (2004). Knowledge about the dangers of smoking is measured by general knowledge of smoking compiled by Martini and Sulistyowati (2005). The measuring tool for categorizing the level of smoking dependence is the FTND (Fagerström Test for Nicotine Dependence) developed by Fagerstro¨m, et al. (1992). This study uses a correlational research design with the pearson correlation statistical processing method. There are two main results from this study. First, there is a non-significant relationship between positive smoking outcome expectancy and knowledge about the dangers of smoking in young adult smokers. Second, there is a significant relationship between the negative smoking outcome expectancy and knowledge about the dangers of smoking in young adult smokers. It is possible that knowledge about the dangers of smoking is not a major predictor of smoking behavior and the smoking outcome expectancy. For people who smoke with a high level of dependence, knowledge does not affect their behavior. Smoking behavior is expected to be a coping stress or physiological mechanism that the body needs.